Experimental and Theoretical Investigation of the Effect of Filler Material on the Performance of Flexible and Rigid Thermoelectric Generators - (:unkn) unknown (My University, 2021)
Thermoelectric generators have found many applications where the heat source can be either flat or curved. For a curved heat source, flexible thermoelectric generators are generally used. A filler material with low thermal conductivity can provide additional mechanical support to the thermoelectric module and can reduce convection and radiation losses. Herein, the effect of three different filler materials on the output performance of rigid and flexible thermoelectric generators is investigated. At first, theoretical models are derived and the experimental study validated the models. The experimental study revealed that the flexible thermoelectric modules outperformed the rigid modules; this is due to the reduction of the number of thermal junctions in the flexible modules and due to the differences in the thermal conductivities of the flexible and rigid substrates. Likewise, among TE modules without filler/with air between the TE legs, with polyurethane foam filler material, and with polydimethylsiloxane filler material, air has the lowest thermal conductivity, and therefore, the thermoelectric generator without filler generates higher output power and higher power density than when the other two filler materials are used. For the fixed temperature gradient, the highest power densities for the flexible and rigid thermoelectric generators without filler are 155 and 137.7 μW/cm2 for temperature gradients of 10.8 and 10.3 °C, respectively.
Keywords: polydimethylsiloxane; curved heat source; filler material; flexible thermoelectric generator; polyimide film; polyurethane foam